تطور مفهوم السببية عند توماس صومائيل كون - شعيبي، عماد فوزي; خليف، منال محمد; حمد، إنصاف (جامعة تشرين, 2019)
يهدف البحث إلى تسليط الضوء على مقاربة كون للعلاقة السببية في الفيزياء، عبر تقصي تطور الأفكار المتعلقة بها، من خلال تحليله لبنية العلم والكشف عن الصعوبات التي خلفها الفهم الخاطئ لتصور السبب، وتقديمه لجانبين هامين للعلاقة السببية، يكمن أحدهما في التحليل المفاهيمي للمصطلح، أما الجانب الثاني، فيتمحور حول وجود تصورين للسببية، أحدهما ضيق والآخر واسع، ولتوضيحهما يقدم أربع مراحل أساسية، تبدأ بمرحلة يطلق عليها أسم مرحلة ما قبل البراديغم، وتليها مرحلة العلم القياسي، ثم تعقبها مرحلة الأزمة، التي تنتهي بمرحلة الثورة العلمية. ويوضح من خلال هذه المراحل تطور تصور السبب من المفهوم الضيق، إلى المفهوم الواسع، والكيفية التي انعكس فيها هذا التطور على المعايير التوضيحية التي يتبناها العلماء في كل مرحلة، وإبراز دور الظروف في تقديم فهم جديد للظواهر وعلاقاتها السببية. وينتهي البحث في استجلاء موقف كون الحقيقي من هذه العلاقة. ولا يتضمن هذا الموقف رفضا لها، وإنما تصحيحا لمسار الدراسة التاريخية للعلاقة السببية.
The research aims at highlighting Kuhn's approach to causal relation in physics through fact-finding the development of its notions, his analysis of the structure of science, revealing the difficulties of the wrong understanding of the concept of cause, and presenting two significant sides of causal relation. The first one contains the conceptual analysis of the term and the other has two concepts of causality, narrow and wide. To explain it, he presents four main Stages. Beginning with a phase called pre-paradigm, followed by the stage of Normal science, followed by the stage of crisis, which ends with the stage of scientific revolution. During these stages, He explains the development of the concept of cause from the narrow one to the wide one and how this development reflects on the explanatory standards that scientists adopt in every stage. Also, he displays the role of circumstances in presenting new understanding of phenomenon and their causal relations. The research ends in clarifying Kuhn's real position on this relation. The position that does not include refusing it, but correcting of the historical study track of causal relation
Keywords: الفلسفة السببية -- الفلسفة الفيزيائية -- كون، توماس صومائيل، ت. 1996 م